"Theory Uncompromised by Practicality": Hybrid ity in Jeffrey Eugenides' "Middlesex." - Shostak, Debra (Contemporary Literature)
This essay examines the literary concept of hybridity as it applies to Jeffrey Eugenides's novel "Middlesex." The protagonist is a hermaphrodite from a family of Greek immigrants. The author contends Eugenides used hybridity in several ways. It refers to the main character's body, cultural identity and to the novel's narrative structure.